Environmental program and its effect on youth’s attitude towards the environment - Nur Syazana Aziz; Nurul Afiqah Mohd Nazzi; Cossicca Tenggok@Lee Eliysia Mohiding; Sonita anak Buyong; Samantha Mae Lim Wee Ping; Getrude Cosmas (Fakulti Psikologi dan Pendidikan, 2021)
The environment is a precious possession that showcases the earth's beauty. However, the condition of the environment has deteriorated in the past decade due to human activities and inability to appreciate the contribution of the environment in our lives. Environmental awareness should be publicized to ensure the earth's sustainability. Therefore, it is important to instill positive attitudes towards the environment. One way to instill a positive attitude towards the environment is by organizing the environmental program by referring to the Yale Model. This may help to create environmental awareness and lead to positive attitudes towards the environment. The study aims to examine youths' attitudes and each of the attitude components (i.e., affective, behaviour, and cognitive) towards the environment before and after the environmental program. The participants were youths aged 15 to 20 (N=29). A set of questionnaires comprising two parts was used. Part A measured the participants' demographic profile, while Part B measured the attitude towards the environment and each attitude component. A similar set of questionnaires was given to participants for the pre- and post-study (i.e., before and after participants completed the one-day program). The Paired Sample t-test showed no significant difference in participants’ attitudes, and each attitude component before and after participants took part in the environmental program. The outcomes of this study are elaborated in the discussion section. The study showed that in organizing an environmental program, the organizers need to identify external factors that might enhance the effectiveness of the attitude change program, besides the Yale Model. For instance, time duration, participants’ ability to access the online environmental program, and the program’s content might affect the effectiveness of the environmental program.